PENGEMBANGAN KOMPETENSI APARATUR DESA (KANTOR DESA SIDODADI KECAMATAN WONGSOREJO KABUPATEN BANYUWANGI) - Faizal Alfian Rozi; Hadi Sunaryo; Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
AbstractVillage Government realizes Apparatus competencies through training, is still less effective and efficient. One reason is that the Apparatus does not understand their respective duties. The purpose of the study was to determine the competency development of Village Apparatus in the Sidodadi Village office. The research method uses a type of qualitative research, with data sources: primary data and secondary data. Then the technique of collecting data, observation, interviews and documentation. While the information determination technique is purposive sampling. The informants were the head of village, village secretary, Head of government affairs, head of government affairs, and head of general affairs. Then the data is analyzed by data reduction, data presentation and data verification. To test the validity of the data using triangulation techniques. The results of the study indicate that the Sidodadi village government in developing competencies is internal. Provide an understandings of administrative skills. Obstacle constraints, among others, senior human resources and inappropriate leadership policies. Keyword: development, competency